Fatty acid and lipid class metabolism of common octopus (Octopus vulgaris) and of European cuttlefish (Sepia officinalis) at early life stages - Reis, Diana Filipa Botelho (2017)
Tese de doutoramento, Ciências do Mar, da Terra e do Ambiente, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2016